2002
DOI: 10.1046/j.1365-3024.2002.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to Schistosoma japonicum cathepsin D aspartic protease

Abstract: Lymphocyte proliferation and cytokine production were measured in groups of mice vaccinated (but not subsequently challenge infected) with recombinant forms of Schistosoma japonicum cathepsin D aspartic protease, rSjASP1 (expressed in bacteria; enzymatically inactive) and rSjASP2 (expressed in insect cells; enzymatically active). Both forms of the schistosome enzyme induced significant proliferation of splenocytes recovered from vaccinated mice, and expression of interferon (IFN)-gamma, interleukin (IL)-4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…By contrast, a significant reduction in IL-4 secretion was observed. Thus, we deduce that the pVIVO 2 SjFABP-23 DNA vaccine may induce a strong Th1 response and suppress Th2 immunity, which was to some extent similar to the results obtained by Zhang et al [13,33]. Previous studies showed that protection was conferred by Th1 cellular immunity with lymphoid proliferation in the region and mediastinal lymph nodes [34], elevated production of IgG4 and IgG2 antibodies, and inhibition of IgE consistently associated with increased susceptibility to reinfection [35].…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, a significant reduction in IL-4 secretion was observed. Thus, we deduce that the pVIVO 2 SjFABP-23 DNA vaccine may induce a strong Th1 response and suppress Th2 immunity, which was to some extent similar to the results obtained by Zhang et al [13,33]. Previous studies showed that protection was conferred by Th1 cellular immunity with lymphoid proliferation in the region and mediastinal lymph nodes [34], elevated production of IgG4 and IgG2 antibodies, and inhibition of IgE consistently associated with increased susceptibility to reinfection [35].…”
Section: Discussionsupporting
confidence: 87%
“…Immunization with the recombinant protein resulted in reduced worm burden in challenged mice but little to no effect in reducing the fecundity of the pathogen. The authors showed that the schistosome protease induced a mixed Th1/Th2 cytokine response (45). Immunization of C57BL/6 mice with recombinant Pep1 of C. posadasii induced a moderate in vitro proliferative response of isolated immune T cells in a recall experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse studies of bacterially expressed and purified recombinant Sj22·6 have demonstrated specific IgG and IgE production but no protection (51). In similar fashion, vaccination with E. coli and baculovirus‐expressed recombinant S. japonicum aspartic protease – cathepsin D – generated high levels of specific antibodies but only a limited level of protection (52–54). Encouraging results have been obtained with recombinant S. japonicum 26‐kDa glutathione S ‐transferase (GST), which induced a pronounced anti‐fecundity effect, as well as a moderate but significant level of protection in terms of reduced worm burden in mice (55), pigs (56) and buffalo (57,58) following experimental or natural challenge infection with S. japonicum .…”
Section: Vaccine Targetsmentioning
confidence: 99%